ANALISIS KELAIKAN TABRAK STRUKTUR HIBRIDA BERDINDING TIPIS DENGAN SUDUT JAMAK PADA KASUS PEMBEBANAN AKSIAL - Fikri Ramdani, Mohamad
Technology that continues to grow becomes a supporting factor to create a safe and comfortable transportation. The crashworthiness analysis of thin-walled structures with variied cross-section geometries has been widely studied. However, the use of hybrid material which is a combination of metal and composite is still rarely done. By using this hybrid material weight reduction can be obtained when compared to aluminum structures and also lower costs when compared to carbon fiber reinforced polymer (CFRP) based structures. In this study, a crash analysis of the feasibility of multiple thin-walled structures with hybrid material was carried out with a case of axial loading. Furthermore, parametric studies were carried out to study the effect of cross section geometry, type of composite material used, orientation and thickness of composites. Modeling is done numerically using the help of LS-DYNA software. From the studies conducted, the octagon-shaped hybrid crashbox structure has a higher crushing force efficiency value than the hybrid structure with square, hexagonal, and circular cross section. The use of hybrid material can reduce the mass of the crashbox up to 11% and increase the specific energy absorption (SEA) by 14%. The mean crushing force value in the hybrid crashbox structure is not the same as the sum of the mean crushing force aluminum with the composite. The use of composite materials in octagonal quasi isotropic aluminum-CFRP hybrid structures provides a reinforcement factor of 2 times on composite structures.